Wealth and its acummulation in Bombay/Mumbai - Motiram, Sripad; Limaye, Kiran (Southern Centre for Inequality Studies (SCIS), 2023)
This paper analyses wealth in Bombay/Mumbai by considering three historical phases: pre-colonial and colonial (sixteenth century-1947), independence to pre-liberalisation (1947-91) and post-liberalisation (1991-present). For the first phase, our geographical focus is Western India and for later phases, it is Mumbai Metropolitan Region and Pune. We rely on various sources: historical accounts, secondary statistical databases, secondary literature and interviews with key informants and wealth owners. We divide wealth owners into three groups: 1000 crores and higher, 1000-100 crores and less than 100 crores (a fuzzy threshold). Colonialism created a wealthy elite through trade and newer industries. The pre-liberalisation period, saw consolidation by some of these (e.g. Tatas) and emergence of new players (e.g. Ambani), who used the regulatory framework. The post-liberalisation phase, created newer opportunities through relaxed regulation and greater space for private sector and foreign capital. The wealth story of Bombay/Mumbai differs from that of other Indian cities. Bombay is essentially a colonial product, and trade (particularly in opium) played a significant role in creating the city and shaping wealth. Banking and finance are much more important for wealth and its accumulation in Mumbai, and this has created a distinct wealth profile for the city.
Keywords: Wealth Inequality; Bombay/Mumbai; Western India; Pre-colonial and colonial (sixteenth century-1947); Independence to pre-liberalisation (1947-91); Post-liberalisation (1991-present)